1996
DOI: 10.1002/chem.19960020207
|View full text |Cite
|
Sign up to set email alerts
|

In Situ 13C Solid‐State NMR and Ex Situ GC–MS Analysis of the Products of tert‐Butyl Alcohol Dehydration on H‐ZSM‐5 Zeolite Catalyst

Abstract: The hydrocarbon products that are formed upon dehydration at 296-673 K of tert-butyl alcohol (tBuOH), adsorbed on H-ZSM-5 zeolite in concentrations equal to that of active Al-OH-Si sites in the catalyst, have been analyzed by 13C solid-state MAS NMR and GC-MS. To facilitate 13C NMR analysis, the alcohol selectively labeled with 13C isotope in the COH group was used. It was found that tBuOH transforms to the adsorbed C, butene dimers plus a trace amount of alkanes at 296 K. Butene dimers exist inside H-ZSM-5 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 70 publications
3
64
0
Order By: Relevance
“…The product distribution for the n-butane conversion on zeolite H-ZSM-5, which is revealed by 13 C MAS NMR spectroscopy, appears to be similar to that typically observed earlier for conjunct polymerization of olefins and alkanes in concentrated sulfuric acid, [38][39][40] for olefins and alcohols on acidic zeolites, [14,27,42] as well as for n-pentane and n-butane conversion on sulfated zirconia. [16,17] It should be emphasized that isobutane (as well as propane) is produced in the course of all stages of the conjunctpolymerization process rather than only through the pure oligomerization-cracking process (Scheme 2) observed earlier (e.g., for the n-butane isomerization on SZ).…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…The product distribution for the n-butane conversion on zeolite H-ZSM-5, which is revealed by 13 C MAS NMR spectroscopy, appears to be similar to that typically observed earlier for conjunct polymerization of olefins and alkanes in concentrated sulfuric acid, [38][39][40] for olefins and alcohols on acidic zeolites, [14,27,42] as well as for n-pentane and n-butane conversion on sulfated zirconia. [16,17] It should be emphasized that isobutane (as well as propane) is produced in the course of all stages of the conjunctpolymerization process rather than only through the pure oligomerization-cracking process (Scheme 2) observed earlier (e.g., for the n-butane isomerization on SZ).…”
Section: Resultssupporting
confidence: 51%
“…The resonances at d = 16.9 and 18.0 ppm belong to the methyl and methylene groups of propane, respectively. [14,16] The intensities of the propane and isobutane signals increase with the reaction time. Propane is the main product at the end of the reaction (Figure 1d).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite claims that a small fraction of 1-octene adsorbed at ambient temperature on H-MFI exhibits carbenium ion properties, evidence from IR [28] and NMR [29] experiments has shown that the proton was .6 -6.…”
Section: Carbenium Ionsmentioning
confidence: 98%